“Ensayo de fertilizacion N P K por densidad de siembra en dos variedades de arroz (oriza sativa L.) (capirona E inia 507- la conquista) en el valle La Conquista-Moyobamba-Perú” - Mori Vela, Jery (2014)
This research was conducted on 29/09/2006 to 03/02/2006 in the valley Conquest, district and province of Moyobamba, San Martin depattamento geographically located at 05 º 50' and 50 º 57' south latitude and 77 º 77 º 12' 05'y west longitude and altitude of 825 msnmm. In which a split plot design sub factorial arrangement of fertilization levels (3), variety (2) and seeding (3) was performed, resulting 18 treatments and 3 replications, making a total of 54 experimental units. Under these considerations, the interest of this study is to precisely find answers in managing levels of fertilization and planting density on the variety Capirona and Conquest, the latter promising for the Alto Mayo and make available to farmers agronomic practicas evaluated to increasing the productivity of rice. The best level of fertilization N3, variety Conquest and seeding density of 02, with a yield of 6.84 tonnes I ha was determined. Keywords: Variety, capirona, conquest, sub plots, fertilization and density.